Can an Emoji a Day Keep the Doctor Away? An Explorative Mixed-Methods Feasibility Study to Develop a Self-Help App for Youth With Mental Health Problems - Van Dam, Levi; Rietstra, Sianne; Van der Drift, Eva; Stams, Geert Jan J. M.; Van der Mei, Rob; Mahfoud, Maria; Popma, Arne; Schlossberg, Eric; Pentland, Alex; Reid, Todd G. (Frontiers in Psychiatry, 2019)
Today’s smartphones allow for a wide range of “big data” measurement, for example, ecological momentary assessment (EMA), whereby behaviours are repeatedly assessed within a person’s natural environment. With this type of data, we can better understand – and predict – risk for behavioral and health issues and opportunities for (self-monitoring) interventions. In this mixed-methods feasibility study, through convenience sampling we collected data from 32 participants (aged 16-24) over a period of three months. To gain more insight into the app experiences of youth with mental health problems, we interviewed a subsample of 10 adolescents who received psychological treatment. The results from this feasibility study indicate that emoji’s (i.e., graphic symbols such as ) can be used to identify positive and negative feelings, and individual pattern analyses of emoji’s may be useful for clinical purposes. While adolescents receiving mental health care are positive about future applications, these findings also highlight some caveats, such as possible drawback of inaccurate representation and incorrect predictions of emotional states. Therefore, at this stage, the app should always be combined with professional counseling. Results from this small pilot study warrant replication with studies of substantially larger sample size.